Eltern und Geschwister als Bildungsressourcen? Der Beitrag von familialem Kapital für Bildungsaspirationen, Selbstkonzept und Schulerfolg von Kindern - Mariana Grgic; Michael Bayer (Journal of Family Research, 2015)
Due to both the growing importance of education for life trajectories and the social structural dependency, the family comes to the fore as the place where social inequalities emerge and are being reproduced. In this contribution, the indicators of family life events – on which quantitative empirical family and education research has been based so far – will be discussed and extended. The focus will be primarily placed on parental support in school issues and on the educational attainment experience of siblings. Based on NEPS data of starting cohort 3, these events will be investigated within the framework of a path analytical model with regard to their explanatory power for the education-related habitus and the school achievements of 5th graders (N=4,661). It can be demonstrated that both aspirations for educational attainment and the school-related as well as the general self-concept of the students are more pronounced when older siblings already had experiences in higher education as well as in the case of parental school-related support of children’s aspirations for educational attainment. Thereby the dependency of expectations of educational attainment and orientations on family resources and family practices related to education can be determined more precisely. This, in turn, serves as a first step aiming at the longitudinally oriented analysis of central intermediation mechanisms of the reproduction of educational inequality within the family.